1997
DOI: 10.1073/pnas.94.22.11881
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of coenzyme pyrroloquinoline quinone and role of Ca 2+ in the catalytic mechanism of quinoprotein methanol dehydrogenase

Abstract: The ab initio structures of 2,7,9-tricarboxypyrroloquinoline quinone (PQQ), semiquinone (PQQH), and dihydroquinone (PQQH2) have been determined and compared with ab initio structures of the (PQQ)Ca 2؉ , (PQQH)Ca 2؉ , and (PQQH2)Ca 2؉ complexes as well as the x-ray structure of (PQQ)Ca 2؉ bound at the active site of the methanol dehydrogenase (MDH) of methyltropic bacteria. Plausible mechanisms for the MDH oxidation of methanol involving the (PQQ)Ca 2؉ complex are explored via ab initio computations and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 33 publications
3
43
1
Order By: Relevance
“…Thus, Ca 2ϩ plays a catalytic role as in the oxidation of CH 3 OH 3 CH 2 O. This finding is in accord with Ca 2ϩ polarizing O5 of PQQ (11). It is to be expected that the interaction of Ba 2ϩ with the developing negative charge at the TS would be greater than that of Ca 2ϩ .…”
Section: Transition State Involving Glu-171-cosupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, Ca 2ϩ plays a catalytic role as in the oxidation of CH 3 OH 3 CH 2 O. This finding is in accord with Ca 2ϩ polarizing O5 of PQQ (11). It is to be expected that the interaction of Ba 2ϩ with the developing negative charge at the TS would be greater than that of Ca 2ϩ .…”
Section: Transition State Involving Glu-171-cosupporting
confidence: 77%
“…1-4). More recently, our attention has been directed to the employment of computational methods, particularly in the mechanism of the oxidation of methanol and glucose by the appropriate quinoprotein enzymes (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…All three structures converged, and apart from the carboxylic group at C-9, which was slightly twisted to form a better hydrogen bond with the proton at N-1, the geometries were approximately planar, in agreement with previous work (30,48). However, it is not our purpose here to discuss all the details of the structures; rather we have concentrated on comparing the experimental and theoretical hfcs.…”
Section: Resultsmentioning
confidence: 51%
“…As shown in Fig. 1, apart from one review (21), reduced PQQ is usually shown protonated at both O-4 and O-5, whereas the radical is depicted singly protonated at either O-4 (30,31) or O-5 (20,24,32), although a deprotonated radical was recently postulated (33). Knowledge of the protonation states is crucial if the ET and proton transfer pathways in both reoxidation steps are to be understood, because depending on the protonation states of the initial and final molecules, the reaction is either simple ET or must be accompanied by the release of a proton.…”
Section: Or Not Protonated At Either O-4 or O-5 A Results That Also Cmentioning
confidence: 99%
“…18 Calcium is also involved in the oxidation of glucose by PQQ-containing glucose dehydrogenases. 19 In the soluble GDH isolated from Acinetobacter calcoaceticus, for which a high-resolution X-ray structure has recently become available, 20 a histidine is found to act as the activesite base.…”
Section: Introductionmentioning
confidence: 99%